Thrombolysis in Myocardial Infarction Frame Count in Single-Vessel Disease After Angioplasty - Chih-Hsuan Yen; Hung-I Yeh; Charles Jia-Yin Hou; Yu-San Chou; Cheng-Ho Tsai (International Journal of Gerontology, 2007)
Background: We compared the thrombolysis in myocardial infarction (TIMI) frame count and examined the impact of angioplasty on the count between patients with normal coronary angiograms and those with single-vessel disease (SVD). Methods: In 780 consecutive patients referred for coronary angiography, TIMI frame count was measured for 149 patients who had SVD and 32 patients with normal angiograms who underwent the procedure for electro-physiologic study or valvular heart disease survey. Results: Comparison of each of the three vessels in the normal vessel group with the corresponding non-stenotic vessels in the SVD group showed similar counts in each of the left anterior descending artery (LAD), left circumflex artery (LCX), and right coronary artery (RCA). For the stenotic vessels, after successful angioplasty, the counts were all reduced (LAD, 54.5 ±28.8 vs. 34.0 ±19.3; LCX, 67.3 ±31.1 vs. 34.1 ±19.0; RCA, 33.2 ±28.1 vs. 19.3 ±7.9; all p <0.05). In addition, the count in the RCA after angioplasty was lower, compared with the RCA of the normal group (19.3 ±7.9 vs. 29.1 ±14.6, p = 0.001). Multivariate analysis showed that the use of oral calcium channel blockers was the only independent predictor for the reduction in RCA after angioplasty. Conclusion: In patients with SVD, the data of TIMI frame count in the nonstenotic vessels were similar to those without the disease, suggesting that the count in the normal artery is not affected by the adjacent stenotic artery. For the stenotic vessels, angioplasty had differential effects on each of the three arteries, indicating the existence of distinct properties, which is affected by calcium channel blockers, for individual coronary arteries in response to atherosclerosis and/or angioplasty.